KESENJANGAN PEMBELAJARAN ILMU PENGETAHUAN ALAM DAN SOSIAL DALAM PENDIDIKAN MITIGASI BENCANA DI SEKOLAH DASAR PADA ERA DIGITAL - Ritonga, Rudi; Ramadhani, Sulistyani Puteri; Amelia, Winda; Alfaruq, Umar (Universitas Trilogi, 2022)
Learning Natural and Social Sciences in elementary schools plays a strategic role in developing students' holistic understanding of natural and social phenomena, including in the context of disaster mitigation education. However, the implementation of Natural And Social Sciences learning in the digital era still faces various gaps that have the potential to hinder students' optimal achievement of disaster mitigation competencies. This study aims to comprehensively examine the gaps in Natural And Social Sciences learning in disaster mitigation education in elementary schools in the digital era. This research used a qualitative approach with a systematic literature study design enriched by conceptual analysis. Data were obtained from reputable scientific articles published between 2018 and 2022 and accessed through the Scopus, Web of Science, ERIC, ScienceDirect, and Google Scholar databases. Data were analyzed using thematic analysis to identify patterns and dimensions of gaps in Natural And Social Sciences learning in the context of disaster mitigation education. The results indicate that gaps in Natural And Social Sciences learning consistently emerge across four main dimensions: curriculum, pedagogy, digital technology utilization, and student mitigation competencies. The largest gap was found in the dimension of digital technology utilization, which is still dominated by the use of technology as a medium for information delivery, followed by gaps in students' mitigation competencies, pedagogical approaches, and curriculum. These findings indicate that although the curriculum provides space for the integration of disaster mitigation education, the implementation of science and natural sciences learning has not fully supported meaningful, contextual learning oriented toward the formation of mitigation behaviors. This study concludes that the gap in science and natural sciences learning in disaster mitigation education stems not only from the curriculum but is more influenced by the weak integration between pedagogy, digital technology, and the disaster context. Therefore, it is necessary to develop inquiry-based science and natural sciences learning integrated with digital technology and the local disaster context to strengthen mitigation competencies and environmental awareness in elementary school students in the digital era.